CARDIOLOGYAcute coronary syndromes in young women – the scale of the problem and the associated risks - Bęćkowski, Maciej (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Diseases of the cardiovascular system mainly affect elderly patients, but they are increasingly often encountered in young individuals. It is estimated that 1 in 20 patients with ischemic heart disease is under the age of 45 years. Only 20% of them are women. According to the PL-ACS register, cases of acute coronary syndromes in young women represent 0.6% of all acute coronary syndrome cases. The most common etiology is atherosclerosis (80%). Other causes include dissections and spasms of the coronary arteries as well as clotting disorders. Smoking tobacco is the most important risk factor, followed by hypertension, hyperlipidemia, and diabetes. The long-term prognosis is usually favorable, but it deteriorates significantly in the event of complications. The literature on this subject is not extensive. Most data come from non-randomized studies of young patients conducted regardless of sex. The purpose of this paper is to present the problem posed by acute coronary syndromes in young women.